Effect of tiger milk mushroom (Lignosus rhinocerus) supplementation on respiratory health, immunity and antioxidant status: an open-label prospective study - Eugenie Sin Sing Tan (Nature Portfolio, 2021)
Abstract Tiger milk mushroom (TMM; Lignosus rhinocerus) have been used for a long time by indigenous communities in South East Asia regions as traditional medicine for different ailments, including respiratory disorders. The beneficial effects of TMM have been proven through in vivo and in vitro models, but these effects have yet to be validated in a clinical study. In this study, the beneficial effects of TMM supplementation were investigated in 50 voluntary participants. Participants were required to take 300 mg of TMM twice daily for three months. Level of interleukin 1β (IL-1β), interleukin 8 (IL-8), immunoglobulin A (IgA), total antioxidant capacity, malondialdehyde (MDA), 3-nitrotyrosine (3-NT), 8-hydroxydeoxyguanosine (8-OHdG), pulmonary function and respiratory symptoms were assessed during baseline and monthly follow-up visits. Results demonstrated that supplementation of TMM significantly (p < 0.05) suppressed the level of IL-1β, IL-8, MDA, as well as respiratory symptoms. In additional to that, TMM also significantly (p < 0.05) induced the level of IgA, total antioxidant capacity, as well as pulmonary function. Analyses of data indicated that gender and BMI were factors influencing the outcomes of antioxidant status. Collectively, our findings suggested that TMM supplementation effectively improves respiratory health, immunity and antioxidant status.